Selección de poblaciones segregantes F3 de arroz provenientes de cruces recíprocos entre Oryza rufipogon G. x Oryza sativa L. spp. japonica, con potencial genético para el desarrollo de nuevas variedades. - Sarcos Berruz, Cristian Jeferson (2018)
VIII. SUMMARY The present research was carried out in the El Palmar sector, CEDEGE project, Babahoyo county, Los Ríos province, located at km 10,5 of the Montalvo highway. It consisted in the evaluation of F3 segregating populations from interspecific crosses between Japonica rice genotypes. The main objective of this study was; select F3 segregating populations of rice from interspecific crosses of Japonica x O. rufipogon (Puyón) for the development of new varieties. The following agronomic variables were evaluated; Vigor, Flowering (days), Vegetative cycle (days), Number of tillers per plant, No. of panicles per plant, Length of the flag leaf (cm), Width of the flag leaf (cm), Length of leaf 2 (cm), Width of leaf 2 (cm), Plant Height (cm), Panicle Length (cm), Grain / panicle, Sterility (%), Shelling (%), 1000 Grain Weight (g), Grain Length (mm), Shelled Grain Width (mm) , White Center (%), Presence of edge (%). The variables for their analysis were subjected to an ANOVA and the Tukey test 5%. In addition a Relative Variability analysis was used for the selection of the upper lines, the analysis of Main Components and the analysis of Conglomerates was also carried out. The results obtained from the present investigation determined that the lines PUYÓN / JP003 P11-64 and PUYÓN / JP003 P11-10 obtained the highest number of panicles per plant and JP004 / PUYÓN P2-87 and PUYÓN / JP003 P7-34 presented greater weight of the 1000 grains, while the PUYÓN / JP003 P11-10 line, obtained the highest number of grains per plant, followed by JP004 / PUYÓN P2-87. The analysis of the relative variability (%) allowed establishing the lines of best production, which were selected as mentioned below: PUYÓN / JP002 P8-32, PUYÓN / JP002 P8-28, PUYÓN / JP003 P11-10, PUYÓN / JP002 P8-31, PUYON / JP002 P8-30, JP003 / PUYON P1-48, PUYON / JP002 P8-29. These lines presented the highest yield weights per plant, and less relative variability (%). It is recommended to continue with the analysis to the selected segregates for F4, because they are considered materials with superior production characteristics. Also, the hybridization works with wild rice species should be continued, since these possess genes of great importance, which can be expressed in future generations, and in this way have a great genetic variability to provide future new alternatives of rice varieties for the rice sector. Keywords: Rice, Japonica, Segregants, Interspecific crosses, Genetic variability.